ANALISIS MANAJEMEN REDAKSI BATAMTODAY.COM PASCA PANDEMI COVID-19 - Febriansyah, Filar Ade; Rorong, Michael Jibrael (SCIENTIA JOURNAL, 2023)
The Batamtoday editorial team is a pioneer of online media in the Riau Islands. Through the presence of Batamtoday, the public can easily access information on a mass scale, anytime and anywhere. This study employs a qualitative descriptive method utilizing the managerialism and organizational democracy theory by Stanley Deetz. This theory demonstrates how communication practices in an organization can distort decision-making. The sub-theories of strategy, agreement, involvement, and participation in organizations provide a contradictory understanding of communication practices in an organization. Strategy and agreement as part of managerialism determine decision-making through leadership domination, while involvement and participation as part of democracy provide a solution to the chaos of domination through leadership movements. The results of the study indicate that the form and pattern of communication applied by the Batamtoday editorial team is verbal, with a communication pattern tailored to the social reality practices within Deetz's concept. The organizational structure in Batamtoday does not give an impression of rigidity in its communication practices. In conclusion, this study shows that the Batamtoday editorial team employs effective communication strategies to build news coverage in the Riau Islands. Communication practices within the editorial team appear flexible and semi-formal, allowing for the involvement and participation of team members in decision-making. Stanley Deetz's managerialism and organizational democracy theory can provide a useful perspective in understanding the dynamics of communication in organizations and how communication strategies can influence decision-making.